Comparison of tracheal intubation with controlled ventilation and laryngeal mask airway with spontaneous ventilation for thoracoscopic bullectomy. Issue 16 (April 2020) - Li, Xiu-Liang; He, Xiang-Bo; Wan, Lei; Liu, Chun-Quan; Cui, Yong
Abstract : Abstract: General anesthesia with double-lumen endobronchial intubation is considered mandatory for thoracoscopic bullectomy. We assessed the safety and feasibility of thoracoscopic bullectomy for treatment of primary spontaneous pneumothorax (PSP) under intubating laryngeal mask airway (ILMA) with spontaneous breathing sevoflurane anesthesia combined with thoracic paravertebral block (TPB). From January 2018 to December 2018, some 34 consecutive patients with PSP were treated by thoracoscopic bullectomy under ILMA with spontaneous breathing sevoflurane anesthesia combined with TPB (study group). To evaluate the safety and feasibility of this new technique, these patients were compared with the control group consisting of 34 consecutive patients with PSP who underwent thoracoscopic bullectomy using tracheal intubation with controlled ventilation from January 2017 to December 2017. The demographic characteristics, intraoperative surgical and anesthetic results, and postoperative results were assessed. The 2 groups had comparable anesthetic time, operation time, chest drainage time, postoperative hospital stays, and hospitalization cost. Visual analogue score (VAS) scores at 3 hours at rest and at coughing were significantly lower in the study group than in the control group (mean, 0.9 vs 2.0 and 1.8 vs 4.0, P  = .024 and P  = .006, respectively). No differences were seen in PaO2 values between the 2 groups in the intraoperative stage and postoperative stage ( P  > .05, respectively). The pH value was significantly lower in the intraoperative stage (mean, 7.28 vs 7.40, P  = .01) and higher in the postoperative stage (mean, 7.35 vs 7.33, P  = .014) in the study group than in the control group. The PaCO2 value was significantly higher in the intraoperative stage in the study group than in the control group (mean, 57.0 mm Hg vs 42.0 mm Hg, P  = .015). In the study group, no cough reflex was found, and the level of collapse of the operative lung was excellent in 31 cases and good in 3 cases. Our study demonstrated that thoracoscopic bullectomy for treatment of PSP can be safely and feasibly performed in highly selected patients under ILMA with spontaneous breathing sevoflurane anesthesia combined with TPB.